Q: What is the answer to 7 plus 3b equals 61?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3b -2 =7 b+4

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

It is a linear equation in two unknown variables, a and b. It can be simplified (slightly) but cannot be solved becasue to solve with two unknowns you need two independent equations. Incidentally, a + 5 = (a - 7) + 12 = (3b + 2) +12 = 3b +14

-45m + 68 = 84m - 61 39m = 7 m = 7/39

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7

Related questions

3b -2 =7 b+4

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

5 + 10ac + 3b

5b plus 5-3b-7 is 2b-2.

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

It is a linear equation in two unknown variables, a and b. It can be simplified (slightly) but cannot be solved becasue to solve with two unknowns you need two independent equations. Incidentally, a + 5 = (a - 7) + 12 = (3b + 2) +12 = 3b +14

-45m + 68 = 84m - 61 39m = 7 m = 7/39

The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3

26 = 3b - 2 - 7b 28 = -4b b = -7

It simplifies to: 3b+17

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7